Damages induced in the woods of some tropical trees during felling (2010)
Merchantable trees in tropical forests are usually widely scattered and the cost of road construction and logging operations are expensive. This calls for finding ways of minimizing felling-induced mechanical damages on wood. This study was carried out to assess and document the magnitude of the incidental damages during the felling of some Nigerian hardwood species in Shasha Forest Reserve in Osun State Nigeria. With utilization potentials and rate of cropping a criteria data were collected with the aid of a checklist on mine species in five different forest stands within the reserve. These include height, diameter, green moisture contents, and estimate of exploitable logs as well as some wood properties. The volume of each tree was computed and the damaged volumes were estimated after felling. Analyses of data were carried out using simple percentages and regression models. Results showed that there are wide variations between and within the studied species with respect of both the tree and wood characteristics. The least average tree height of 40.39m was recorded for Mansonia altissima while the highest average tree height of 56.61m was recorded for Khaya Ivorensis. Merchantable tree volume ranged from 13.68m3 for Mansonia to 46.25m3 for Entandrophragma angolensis while green density ranged from 936.91kg/m3 tp 1845.95kg/m3 and moisture content ranged and 108.09% and 147.05% respectively. Visual assessment of damage volume shows that the degree of damage expressed as a percentage in the studied species ranged between 6.25% and 13.15%. The average damage volume per species is between 7.39% and 12.66% for the selected species. The regression models revealed that the magnitude of the damage portion has significant relationship with tree height, volume and weight.